Opioids and TRPV1 in the peripheral control of neuropathic pain – Defining a target site in the injured nerve. (February 2016) - Labuz, Dominika; Spahn, Viola; Celik, Melih Özgür; Machelska, Halina
Abstract: Targeting peripheral neuropathic pain at its origin may prevent the development of hypersensitivity. Recently we showed this can be mediated by opioid receptors at the injured nerve trunk. Here, we searched for the most relevant peripheral site to block transient receptor potential vanilloid 1 (TRPV1), and investigated analgesic interactions between TRPV1 and opioids in neuropathy. In a chronic constriction injury (CCI) of the sciatic nerve in mice, we assessed the effects of μ-, δ- and κ-opioid receptor agonists and TRPV1 antagonist (SB366791) injected at the CCI site or into the injured nerve-innervated paw on spontaneous paw lifting, heat and mechanical sensitivity. We also examined TRPV1 expression in total membrane and plasma membrane fractions from nerves and paws. We found that opioids and SB366791 co-injected in per se nonanalgesic doses at the CCI site or into the paw diminished heat and mechanical sensitivity. SB366791 alone dose-dependently alleviated heat and mechanical sensitivity. TRPV1 blockade in the paw was more effective than at the CCI site. None of the treatments diminished spontaneous paw lifting. TRPV1 expression analysis suggests that the levels of functional TRPV1 do not critically determine the TRPV1 antagonist-mediated analgesia. Together, the identification of the primary action site in damaged nerves is crucial for effective pain control. Contrary to opioids, the TRPV1 blockade in the injured nerve peripheral terminals, rather than at the nerve trunk, appears promising against heat pain. Opioid/TRPV1 antagonist combinations at both locations partially reduced neuropathy-triggered heat and mechanical pain. Highlights: Peripheral TRPV1 blockade alleviates neuropathic pain. TRPV1 antagonist is more effective after intraplantar than perineural injection. Opioid/TRPV1 antagonist combinations at both locations are partially effective. Primary action site identification in damaged nerves is crucial for efficient analgesia.